Insertion Tendinosis of Stylomandibular Ligament: Ernest Syndrome. Issue 3 (May 2021) - Jose, Anson; Rawat, Aditi; Nagori, Shakil Ahmed
Abstract : Abstract: Insertion tendinosis of stylomandibular ligament (SML) or Ernest syndrome is a very rare and under reported head and neck pain disorder. The pain originates from the insertion of stylomandibular region and radiates to the temple, lateral side of the neck and temporomandibular joint (TMJ). The diagnosis is confirmed by palpation of SML and local anesthetic block at the insertion of SML. The authors report 4 patients who presented with chronic pain which radiated to the TMJ and temple and did not respond to conservative management. All patients after diagnosed with Local anesthetic block were given methylprednisolone injection at the insertion of SML. Complete remission of pain was seen at 12 months of follow up without any recurrence. Craniofacial surgeons involved in the treatment of various head and neck pain should include this less documented syndrome in their differential diagnosis when treating TMJ disorders.